Self-compassion and suicide risk: a moderated mediation model and evidence from Chinese universities - Ge, Dandan (Frontiers in Psychology, 2023)
To investigate the relationship between self-compassion (positive and negative) and suicidal risk, and to analyze the mediating effect of negative emotion and the moderating effect of resilience.1143 College students were surveyed by using Chinese Self-Compassion Scale(CSCS), Depression Anxiety Stress Scale-21 Chinese Version(DASS-21), Connor-Davidson Resilience Scale(CD-RISC) and Suicidal Behavior Questionnaire-Revised(SBQ-S).The result shows that: negative self-compassion had a significant positive predictive effect on college students' suicide risk; in the model of negative self-compassion affecting suicide risk, negative emotions played a mediating role and the mediating role was moderated by resilience. Specifically, compared with low resilience, students with high resilience have a weaker ability to predict suicide risk by negative emotions. The findings suggest that negative self-compassion is a risk factor for suicide risk, transforming negative self-compassion and enhancing resilience has a guiding effect on suicide prevention and intervention.